2012
DOI: 10.1016/j.ijrobp.2011.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Imaging Biomarkers of Postradiotherapy Xerostomia

Abstract: Purpose Xerostomia is a major complication of head and neck radiotherapy. Available xerostomia measures remain flawed. FDG-PET/CT is routinely used for staging and response assessment of head and neck cancer. We investigated quantitative measurement of parotid gland FDG uptake as a potential biomarker for post-radiotherapy xerostomia. Methods and Materials Ninety-eight locally advanced head and neck cancer patients receiving definitive radiotherapy underwent baseline and post-radiotherapy FDG-PET/CT on a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Other studies have shown that parotid gland SUVs decrease post-radiotherapy, and in addition that this change was associated with parotid gland dose [37,38]. Cannon et al [38] showed that mean 'SUV-weighted parotid gland dose (voxel-wise)' was significantly related to fractional-SUV (post-SUV/pre-SUV). In an additional small cohort (n = 8), they showed that fractional-SUV was significantly associated with fractional salivary flow and physician-rated xerostomia.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown that parotid gland SUVs decrease post-radiotherapy, and in addition that this change was associated with parotid gland dose [37,38]. Cannon et al [38] showed that mean 'SUV-weighted parotid gland dose (voxel-wise)' was significantly related to fractional-SUV (post-SUV/pre-SUV). In an additional small cohort (n = 8), they showed that fractional-SUV was significantly associated with fractional salivary flow and physician-rated xerostomia.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, a few studies have recently proposed novel models to quantify or predict normal tissue radiation toxicity using functional information from FDG‐PET , single photon emission computed tomography perfusion , and DCE‐MRI . These studies, that propose new metrics as the metabolic dose, functional dose or bio ‐dose, show an emerging interest toward an innovative approach to RT that integrates into the treatment strategies the individual differences in tumor biology and radiation sensitivity of normal tissues .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented the utility of noninvasive imaging techniques, e.g., scintigraphy, [ 18 F]fluorodeoxyglucose-labeled positron emission tomography (FDG-PET), and ultrasound for quantitatively evaluating the salivary function (7,8). MR sialography, as well as dynamic contrast-enhanced MRI (DCE MRI), and diffusion-weighted imaging (DWI) have also been used to investigate the radiation damage to salivary glands (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…In addition, the apoptotic response seen after irradiation was dependent on p53 expression. Cannon et al 149 demonstrated radiotherapy toxicity to the parotid gland by means of fluorodeoxyglucose-labelled positron emission tomography-computed tomography (FDG-PET-CT).…”
Section: Radiotherapymentioning
confidence: 99%